Recommendations of the project group prevention of the German Cardiac Society (DGK) on risk-adjusted prevention of cardiovascular diseases*Part 4: Platelet function inhibitors, hormone replacement therapy, behavioural and psychosocial risk factors Empfehlungen der Projektgruppe Prävention der DGK zur risikoadjustierten Prävention von Herz- und Kreislauferkrankungen Teil 4: Thrombozytenfunktionshemmer, Hormonersatztherapie, Verhaltensänderung und psychosoziale Risikofaktoren - Gohlke, H.; Albus, C.; Bönner, G.; Darius, H.; Eckert, S.; Gohlke-Bärwolf, C.; Gysan, D.; Hahmann, H.; Halle, M.; Hambrecht, R.; Mathes, P.; Predel, H. G.; et al. (Der Kardiologe, 2013)
Platelet inhibitors. In patients with vascular diseases platelet inhibitors are usually administered as long-term medication. In patients without vascular diseases they are indicated for preventive reasons only in patients with high cardiovascular risk (≥5% SCORE or ≥20% PROCAM) taking risks and side effects into account. In patients with type 2 diabetes without vascular disease platelet inhibitors are not indicated.Hormone replacement therapy. Cardiovascular diseases are the most important causes of death in menopausal women. Although observational studies and mechanistic studies have suggested a preventive effect hormone replacement therapy does not prevent cardiovascular events and is not indicated. There is an increased risk of thromboembolism with hormone replacement therapy. If it is used for symptomatic reasons the best possible control of all cardiovascular risk factors should be attempted.Lifestyle modification and psychosocial risk factors. Long-term adherence to complex medication regimens and to a healthy lifestyle frequently suffers from low acceptance. Persons with low socioeconomic status and/or low education are particularly at risk. Non-guideline adherent medication and an unfavourable lifestyle are associated with a higher cardiac event rate. Social isolation, chronic familial or vocational stress, fear of side effects of medications, low motivation and (frequently unrecognized) nicotine dependence contribute to decreased adherence. Increased attention to these factors and in particular an individually adapted communication procedure taking these patient factors into account can mitigate these problems. A 10-item program is proposed to improve communication and adherence to treatment. © Springer-Verlag Berlin Heidelberg 2012.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Health behavior; Hormone replacement therapy; Platelet aggregation inhibitors; Psychosocial interventions; Vascular diseases